Surface treating agent for positive electrode material of lithium ion battery and application of surface treating agent

By using surface treatment agents of monosaccharides and oligomeric sugar substances, combining the strong sugar ring structure with the transition metal on the surface of the positive electrode material, the serious side reaction problem at high voltage is solved, and the higher Coulomb efficiency and capacity are achieved Retention rate.

CN119447300AActive Publication Date: 2025-02-14CENT SOUTH UNIV
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411518805.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-14
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

At high voltage, there is a serious side reaction between the transition metal and the electrolyte of the positive electrode material of the lithium-ion battery, resulting in the dissolution of transition metal and the decomposition of ester solvents, forming an interface film that hinders the diffusion of lithium ions.

Method used

Using surface treatment agents including monosaccharides and oligomeric sugar substances, the transition metal on the surface of the positive electrode material is formed through the sugar ring structure, reducing the solvation effect of the electrolyte on the metal, and stable through the oxidation and decomposition of the sugar ring. And a substance with fast ion conductivity protects the positive electrode material.

Benefits of technology

It effectively reduces the dissolution of transition metals and the decomposition of ester solvents, reduces the generation of interface films, improves the transmission efficiency of lithium ions, and enhances the coulomb efficiency and capacity retention rate of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447300A_ABST
    Figure CN119447300A_ABST
Patent Text Reader

Abstract

The invention discloses a surface treating agent for a positive electrode material of a lithium ion battery and application of the surface treating agent. The surface treating agent of the lithium ion battery positive electrode material disclosed by the invention comprises monosaccharide or oligosaccharide. The monosaccharide comprises one or more of aldose and ketose; and the oligosaccharide comprises one or more of lactose, fructo-oligosaccharide, maltose, cellobiose, trehalose, raffinose, pinotriose and gentiotriose. The surface treating agent forms a strong binding force with the transition metal on the surface of the positive electrode material, so that the solvation effect of the ester solvent in the electrolyte on the surface transition metal is weakened, and the surface transition metal is prevented from being dissolved in the electrolyte and deposited on the negative electrode side. Meanwhile, the catalytic decomposition process of the surface transition metal on the electrolyte in the process is weakened, so that the decomposition of the electrolyte on the surface of the high-voltage material is weakened and inhibited, the deposition of electrolyte decomposition products on the positive electrode side is reduced, and the circulation of the battery is more stable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new energy, and in particular relates to a surface treatment agent for a lithium ion battery positive electrode material and an application thereof. Background Art

[0002] In the context of the rapid development of lithium-ion batteries, people have put forward higher requirements for the energy density of lithium-ion batteries. In order to achieve higher energy density, on the one hand, the specific capacity of the positive electrode material can be increased, and on the other hand, the discharge voltage of the material can be increased. In the process of pursuing high voltage, researchers have continuously increased the working voltage of positive electrode materials by increasing the cutoff voltage of lithium cobalt oxide (LCO) and nickel cobalt manganese oxide ternary materials (NCM), adding Mn to lithium iron phosphate to synthesize lithium iron manganese phosphate (LFMP), and adding Ni to lithium manganese oxide to synthesize lithium nickel manganese oxide (LNMO), thereby obtaining higher energy density. The current maximum cutoff voltage of LCO and NCM523 positive electrode materials can reach about 4.6V, the cutoff voltage of LFMP is generally 4.5V, and the cutoff voltage of LNMO reaches 4.9V. At such a high voltage, the transition metal on the surface of the positive electrode material particles and the electrolyte directly often have serious side reactions. Under high voltage, since the surface transition metal is in a high valence state and there are fewer electrons around the transition metal, it is easy to undergo a strong solvation reaction with the ester solvent in the electrolyte, which reduces the TM-O strength and gives the transition metal more opportunities to dissolve in the electrolyte. At the same time, this solvation reaction will also intensify the decomposition of the ester solvent itself. On the one hand, its decomposition products are deposited on the surface of the positive electrode particles to form a thicker positive electrode / electrolyte interface (CEI) film, which hinders the diffusion of lithium ions, and some of the products overflow in the form of gas.

[0003] Researchers have proposed some solutions to these serious problems on the surface of high-voltage materials, such as coating with inert substances such as Al2O3 to reduce the attack of the electrolyte on the surface transition metals; coating with fast ion conductors such as Li3PO4 to accelerate the transmission of surface ions to improve kinetic performance. However, although coating with inert substances can partially alleviate side reactions, it also hinders the transmission of lithium ions; coating with fast ion conductors, although it improves kinetic performance, is helpless against side reactions. Therefore, it is urgent to find some low-cost surface treatment agents that can effectively alleviate side reactions between transition metals and electrolytes at high voltages to prevent transition metal dissolution, while not affecting the ion diffusion process. Summary of the invention

[0004] One of the purposes of the present invention is to provide a surface treatment agent for lithium ion positive electrode materials, which is used to address the problem of strong side reactions between high voltage materials and electrolytes and to improve the capacity retention rate and coulombic efficiency of the materials.

[0005] A second object of the present invention is to provide a method for preparing a battery positive electrode material comprising the surface treatment agent of the lithium ion positive electrode material.

[0006] The invention provides a surface treatment agent for lithium ion positive electrode materials, comprising monosaccharide and oligomeric saccharide substances.

[0007] Furthermore, the monosaccharide includes one or more of aldose and ketose.

[0008] Furthermore, the oligomeric carbohydrate substances include one or more of lactose, oligofructose, maltose, cellobiose, trehalose and raffinose.

[0009] Furthermore, the sugar ring of the surface treatment agent contains -OH and -CH2OH hydrophilic groups; the surface treatment agent includes a chain structure composed of sugar rings; the chain structure includes a branched chain structure and an unbranched chain structure; the protons on the hydroxyl groups in the chain structure can be Li + 、Na + , Ca + , K + The metal ions are substituted to form the corresponding alcohol salts.

[0010] The present invention also provides an application of the surface treatment agent for the lithium ion positive electrode material, using the surface treatment agent to treat and prepare the positive electrode material of the battery, comprising the following steps:

[0011] S1. The surface treatment agent is dissolved in water at a set mass ratio, and after complete dissolution, the positive electrode material of the battery is added, and stirred at a preset temperature until the water is completely evaporated to obtain material 1;

[0012] S2. Dry the material 1 obtained in step S1 in an oven to obtain a surface-treated battery positive electrode material.

[0013] Furthermore, the surface treatment agent for the lithium ion positive electrode material may be used by a spray drying process.

[0014] Furthermore, in step S1, the set mass ratio is 0.1-1%; the preset temperature is 40-80°C; preferably, the set mass ratio is 0.2-0.5%; the preset temperature is 50-60°C; the battery positive electrode material is at least one of LiXO2, LiY2O4, and LiZPO4; wherein X is at least one of Ni, Mn, and Co; Y is at least one of Ni and Mn; and Z is at least one of Fe and Mn.

[0015] Specifically, the battery positive electrode material includes lithium iron phosphate LiFePO4, lithium iron manganese phosphate LiMn x Fe1-x PO4, lithium manganese oxide LiMn2O4, lithium nickel manganese oxide LiNi 0.5 Mn 1.5 O4, nickel-cobalt-manganese ternary material LiNi x Co y Mn 1-x-y One or more of O2 and lithium cobalt oxide LiCoO2.

[0016] Preferably, the battery positive electrode material includes lithium manganese iron phosphate LiFe 0.4 Mn 0.6 PO4, lithium manganese oxide LiMn2O4, lithium nickel manganese oxide LiNi 0.5 Mn 1.5 O4, medium nickel ternary LiNi 0.5 Co 0.2 Mn 0.3 O2, lithium cobalt oxide LiCoO2 or one or more thereof.

[0017] Further preferably, the battery positive electrode material comprises lithium manganese iron phosphate LiFe 0.4 Mn 0.6 PO4, LiNi nickel manganese oxide 0.5 Mn 1.5 O4, lithium cobalt oxide LiCoO2 and medium nickel ternary LiNi 0.5 Co 0.2 Mn 0.3 O2.

[0018] Furthermore, step S2 specifically involves drying the material 1 obtained in step S1 at 100-150° C. for 6-24 hours to obtain a surface-treated battery positive electrode material.

[0019] Principle of the present invention:

[0020] The present invention uses monomeric and oligomeric sugar substances as surface treatment agents for positive electrode materials of lithium ion batteries. The sugar ring structure in the surface treatment agent has a stronger binding force with the transition metal on the surface of the positive electrode material. This strong binding force weakens the solvation effect of the ester solvent in the electrolyte on the transition metal on the surface of the positive electrode material, and reduces the dissolution of the transition metal into the electrolyte. At the same time, due to the strong binding force between the sugar ring structure in the surface treatment agent and the transition metal on the surface of the positive electrode material, the high-valent electron-deficient surface transition metal on the positive electrode material of the lithium ion battery under high voltage is more inclined to attack the sugar ring structure on the surface rather than the ester solvent in the electrolyte. This process also inhibits the decomposition of the electrolyte, reducing the amount of decomposition products, including deposition on the surface of the positive electrode particles and overflow in the form of gas. In addition, the oxidation process of the sugar ring often occurs simultaneously with the formation process of the CEI film, that is, the oxidation of the sugar ring participates in the film formation process. At the same time, the oxidation products of the sugar ring contain more stable and difficult-to-oxidize -COO- substances, and both -COO- and -OH have good coordination effects on the dissolved transition metals. Not only that, the sugar ring participates in the film formation process through its own oxidation and decomposition, and the generated -COO- substances tend to partially combine with Li+ to produce -COOLi, a fast ion conductor, accelerating the kinetic process. By alleviating the decomposition of the electrolyte under high pressure and oxidizing to generate more stable substances with faster ionic conductivity to protect the high-voltage positive electrode material, the coulombic efficiency and capacity retention rate during the cycle can be improved.

[0021] Beneficial effects of the present invention:

[0022] (1) The strong binding force between the surface treatment agent provided by the present invention and the surface transition metal weakens the solvation effect of the ester solvent in the electrolyte on the surface transition metal, greatly reducing the dissolution of the surface transition metal in the electrolyte in this way;

[0023] (2) The sugar rings in the surface treatment agent provided by the present invention have a large binding force with the transition metal on the surface of the positive electrode material, so that the surface transition metal preferentially attacks the sugar substance under high voltage and preferentially oxidizes and decomposes under high voltage, thereby preventing the rapid decomposition of ethylene carbonate (EC) carbonate solvents under high voltage and avoiding the formation of a thick CEI film, thereby promoting ion transmission;

[0024] (3) The oxidative decomposition product -COO- of the sugar ring in the surface treatment agent provided by the present invention on the positive electrode material under high voltage conditions and the large amount of -OH contained in the sugar ring itself have a relatively obvious coordination and complexing effect on the transition metal, inhibiting the dissolution of the transition metal into the electrolyte and the deposition on the negative electrode, effectively improving the coulombic efficiency and cycle stability of the high voltage positive electrode material;

[0025] (4) The product -COO- of the oxidation decomposition of the sugar ring in the surface treatment agent provided by the present invention on the positive electrode material under high voltage will partially combine with Li+ to produce -COOLi, a fast ion conductor, to accelerate the kinetic process. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The cycle diagram of Example 1, Example 2, Example 3, Example 4 and Comparative Example 1 at room temperature (25° C.), 1C;

[0027] Figure 2 The cycle diagram of Example 1, Example 2, Example 3, Example 4 and Comparative Example 1 at high temperature (60° C.), 1C;

[0028] Figure 3 The coulombic efficiency of Example 1, Example 2, Example 3, Example 4 and Comparative Example 1 at room temperature (25° C.) and 0.1C cycle;

[0029] Figure 4 The membrane impedance Rf of Example 1, Example 2, Example 3, Example 4 and Comparative Example 1 after cycling.

[0030] Figure 5 The manganese deposition amount on the negative electrode side after cycles of Example 1, Example 2, Example 3, Example 4 and Comparative Example 1.

[0031] Figure 6 The rate performances of Example 1, Example 2, Example 3, Example 4, and Comparative Example 1 are shown.

[0032] Figure 7 The manganese content dissolved in the electrolyte is shown in Figure 1, Figure 2, Figure 3, Figure 4 and Comparative Example 1 when they are immersed in the electrolyte at 55°C. DETAILED DESCRIPTION

[0033] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0034] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0035] Example 1

[0036] In this embodiment, glucose is used as a surface treatment agent. Glucose is dissolved in water at a mass ratio of 1 wt %. After glucose is completely dissolved, lithium nickel manganese oxide (LiNi 0.5 Mn1.5 O4), stirred at 60°C until the water was completely evaporated, and the evaporated material was dried in an oven at 120°C for 12h to obtain the surface-treated LiNi 0.5 Mn 1.5 O4.

[0037] The surface treated LiNi 0.5 Mn 1.5 O4: conductive additive (conductive carbon black): PVDF (based on the total weight of the initiating solute) are prepared into a slurry in a weight ratio of 80:10:10, and then coated on an aluminum foil and dried at 120°C for 8h to obtain a positive electrode sheet of the battery.

[0038] Cut the positive electrode sheet of the battery into a disc with a diameter of 12mm for standby use. The battery is assembled in a super-purified glove box, and the button half-cell is assembled in the order of positive electrode shell, positive electrode disc, electrolyte, diaphragm, electrolyte, lithium metal disc, foam nickel mesh and negative electrode shell. After the assembly is completed, let it stand for 4-6 hours, take the battery at 25℃ and 60℃, respectively, and perform electrochemical cycle tests in the blue electricity system. After activating 3 cycles at 0.1C, 0.2C and 0.5C, perform room temperature and high temperature cycle tests at a current density of 1C. The cycle at low rate is electrochemically cycled at 25℃ in the blue electricity system, and the charge and discharge current is 0.1C (1C = 148mA / g). There are no special requirements for the electrolyte used. It is a common ester electrolyte with good lithium ion transmission capacity in the industry {the electrolyte in this case is 1MLiPF6+ethylene carbonate (EC): dimethyl carbonate (DMC): ethyl methyl carbonate (EMC) = 1:1:1, volume ratio, and 3wt% of fluoroethylene carbonate (FEC) is added}. The voltage window for charge and discharge is: 3.5~4.9V.

[0039] The assembled button cell was cycled at room temperature at 1C. Figure 1 As shown in Figure 1, the capacity retention rate after 100 cycles reached 92.3%. Figure 2 As shown in Figure 1, the capacity retention rate after 60 cycles reached 89.32%. The coulombic efficiency under 0.1C low current charging and discharging at room temperature is shown in Figure 1. Figure 3 As shown in Figure 1, its coulombic efficiency at low current is higher than that of comparative example 1. The membrane impedance Rf after the cycle is as follows: Figure 4 As shown in Figure 2, the amount of Mn deposited on the negative electrode after cycling is as follows: Figure 5 shown.

[0040] The battery obtained in Example 1 was tested for rate performance by charging and discharging at 0.1C, 0.5C, 1C, 2C, 5C, and 10C. The rate performance is shown in FIG. Figure 6 shown.

[0041] At the same time, the surface treated LiNi 0.5 Mn 1.5 O4 was immersed in the common electrolyte mentioned above, 1g of material was immersed in 10ml of electrolyte. It was immersed for two weeks at 55℃, and the manganese content in the electrolyte was detected by ICP to verify the effect of surface treatment on reducing the solvation of surface manganese by the electrolyte. The ICP results are as follows Figure 7 shown.

[0042] Example 2

[0043] Compared with Example 1, the only difference is that lactose is used as the surface treatment agent, and the lactose is dissolved in water at a mass ratio of 0.5wt%. After the lactose is completely dissolved, the positive electrode material lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 O4), stirred at 80°C until the water was completely evaporated, and the evaporated material was dried in an oven at 150°C for 24h to obtain the surface-treated LiNi 0.5 Mn 1.5 O4, the other processing procedures are the same as those in Example 1.

[0044] The assembled button cell was cycled at room temperature at 1C. Figure 1 As shown in Figure 1, the capacity retention rate after 100 cycles reached 95.0%. Figure 2 As shown in Figure 1, the capacity retention rate after 60 cycles reached 93.0%. The coulombic efficiency under 0.1C low current charging and discharging at room temperature is shown in Figure 1. Figure 3 As shown in Figure 1, its coulombic efficiency at low current is higher than that of comparative example 1. The membrane impedance Rf after the cycle is as follows: Figure 4 As shown in Figure 2, the amount of Mn deposited on the negative electrode after cycling is as follows: Figure 5 shown.

[0045] The battery obtained in Example 2 was tested for rate performance by charging and discharging at 0.1C, 0.5C, 1C, 2C, 5C, and 10C. The rate performance is shown in FIG. Figure 6 shown.

[0046] The ICP results of the surface treated material in Example 2 after being immersed in the electrolyte are as follows: Figure 7 shown.

[0047] Example 3

[0048] Compared with Example 1, the only difference is that melezitose is used as the surface treatment agent, melezitose is dissolved in water at a mass ratio of 0.2 wt%, and after it is completely dissolved, the positive electrode material lithium nickel manganese oxide (LiNi 0.5 Mn 1.5O4), stirred at 40 ° C until the water is completely evaporated, and the evaporated material is dried in an oven at 100 ° C for 6 h to obtain the surface-treated LiNi 0.5 Mn 1.5 O4, the other processing procedures are the same as those in Example 1.

[0049] The assembled button cell was cycled at room temperature at 1C. Figure 1 As shown in Figure 1, the capacity retention rate after 100 cycles reached 96.0%. Figure 2 As shown in Figure 1, the capacity retention rate after 60 cycles reached 97.1%. The coulombic efficiency under 0.1C low current charging and discharging at room temperature is shown in Figure 1. Figure 3 As shown in Figure 1, its coulombic efficiency at low current is higher than that of comparative example 1. The membrane impedance Rf after the cycle is as follows: Figure 4 As shown in Figure 2, the amount of Mn deposited on the negative electrode after cycling is as follows: Figure 5 shown.

[0050] The battery obtained in Example 3 was tested for rate performance by charging and discharging at 0.1C, 0.5C, 1C, 2C, 5C, and 10C. The rate performance is shown in FIG. Figure 6 shown.

[0051] The ICP results of the surface treated material obtained in Example 3 after being immersed in the electrolyte are as follows: Figure 7 shown.

[0052] Example 4

[0053] Compared with Example 1, the only difference is that raffinose is used as the surface treatment agent, and raffinose is dissolved in water at a mass ratio of 0.1 wt%. After the raffinose is completely dissolved, the positive electrode material lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 O4), stirred at 50°C until the water was completely evaporated, and the evaporated material was dried in an oven at 120°C for 12h to obtain the surface-treated LiNi 0.5 Mn 1.5 O4, the other processing procedures are the same as those in Example 1.

[0054] The assembled button cell was cycled at room temperature at 1C. Figure 1 As shown in Figure 1, the capacity retention rate after 100 cycles reached 96.0%. Figure 2 As shown in Figure 1, the capacity retention rate after 60 cycles reached 97.1%. The coulombic efficiency under 0.1C low current charging and discharging at room temperature is shown in Figure 1. Figure 3 As shown in Figure 1, its coulombic efficiency at low current is higher than that of comparative example 1. The membrane impedance Rf after the cycle is as follows: Figure 4 As shown in Figure 2, the amount of Mn deposited on the negative electrode after cycling is as follows: Figure 5 shown.

[0055] The battery obtained in Example 4 was tested for rate performance by charging and discharging at 0.1C, 0.5C, 1C, 2C, 5C, and 10C. The rate performance is shown in FIG. Figure 6 shown.

[0056] The ICP results of the surface treated material obtained in Example 4 after being immersed in the electrolyte are as follows: Figure 7 shown.

[0057] Example 5

[0058] Compared with Example 1, the only difference is that the positive electrode material is lithium cobalt oxide LiCoO2, the charge and discharge voltage window is 3.0-4.6V, and the other processing procedures are the same as those in Example 1.

[0059] The 1C cycle data of the assembled button battery at room temperature are shown in Table 1. After 100 cycles, the capacity retention rate is 87.2%, which is higher than that of Comparative Example 2.

[0060] Example 6

[0061] Compared with Example 2, the only difference is that the positive electrode material is lithium cobalt oxide LiCoO2, the charge and discharge voltage window is 3.0-4.6V, and the other processing procedures are the same as those in Example 2.

[0062] The 1C cycle data of the assembled button battery at room temperature are shown in Table 1. After 100 cycles, the capacity retention rate is 86.3%, which is higher than that of Comparative Example 2.

[0063] Example 7

[0064] Compared with Example 1, the only difference is that the positive electrode material is lithium nickel cobalt manganese oxide LiNi 0.5 Co 0.2 Mn 0.3 O2, the charge and discharge voltage window is 2.8-4.6V, and the other processing procedures are the same as those in Example 1.

[0065] The 1C cycle data of the assembled button battery at room temperature are shown in Table 1. After 100 cycles, the capacity retention rate is 92.0%, which is higher than that of Comparative Example 3.

[0066] Example 8

[0067] Compared with Example 2, the only difference is that the positive electrode material is lithium nickel cobalt manganese oxide LiNi 0.5 Co 0.2 Mn 0.3 O2, the charge and discharge voltage window is 2.8-4.6V, and the other processing procedures are the same as those in Example 2.

[0068] The 1C cycle data of the assembled button battery at room temperature are shown in Table 1. After 100 cycles, the capacity retention rate is 94.2%, which is higher than that of Comparative Example 3.

[0069] Example 9

[0070] Compared with Example 1, the only difference is that the positive electrode material is lithium iron manganese phosphate LiFe 0.4 Mn 0.6 PO4, the charge and discharge voltage window is 2.5-4.5V, and the other processing procedures are the same as those in Example 1.

[0071] The 1C cycle data of the assembled button battery at room temperature are shown in Table 1. After 100 cycles, the capacity retention rate is 98.1%, which is higher than that of Comparative Example 4.

[0072] Example 10

[0073] Compared with Example 2, the only difference is that the positive electrode material is lithium iron manganese phosphate LiFe 0.4 Mn 0.6 PO4, the charge and discharge voltage window is 2.5-4.5V, and the other processing procedures are the same as those in Example 2.

[0074] The 1C cycle data of the assembled button battery at room temperature are shown in Table 1. After 100 cycles, the capacity retention rate is 98.6%, which is higher than that of Comparative Example 4.

[0075] Comparative Example 1

[0076] Compared with Example 1, the only difference is that no surface treatment agent is used to treat the surface of the positive electrode material, and the rest of the treatment process is the same as Example 1.

[0077] The assembled button cell was cycled at room temperature at 1C. Figure 1 As shown, the 1C cycle at high temperature is Figure 2 As shown, the coulombic efficiency under 0.1C low current charging and discharging at room temperature is as follows Figure 3 The membrane impedance Rf after the cycle is as follows Figure 4 As shown in Figure 2, the amount of Mn deposited on the negative electrode after cycling is as follows: Figure 5 shown.

[0078] The battery obtained in Comparative Example 1 was tested for rate performance by charging and discharging at 0.1C, 0.5C, 1C, 2C, 5C, and 10C, respectively. The rate performance is shown in FIG. Figure 6 shown.

[0079] The ICP results of the surface treated material obtained in Comparative Example 1 after immersion in the electrolyte are as follows: Figure 7shown.

[0080] Comparative Example 2

[0081] Compared with Comparative Example 1, the only difference is that the positive electrode material used is replaced with lithium cobalt oxide LiCoO2, and the rest of the processing process is the same as Comparative Example 1.

[0082] The 1C cycle data of the assembled button battery at room temperature are shown in Table 1. After 100 cycles, the capacity retention rate is 81.9%.

[0083] Comparative Example 3

[0084] Compared with Comparative Example 1, the only difference is that the positive electrode material used is replaced with lithium nickel cobalt manganese oxide LiNi 0.5 Co 0.2 Mn 0.3 O2, and the rest of the treatment process is the same as that of Comparative Example 1.

[0085] The 1C cycle data of the assembled button battery at room temperature are shown in Table 1. The capacity retention rate after 100 cycles is 89.6%.

[0086] Comparative Example 4

[0087] Compared with Comparative Example 1, the only difference is that the positive electrode material used is replaced with lithium iron manganese phosphate LiFe 0.4 Mn 0.6 PO4, and the rest of the treatment process is the same as that of Comparative Example 1.

[0088] The 1C cycle data of the assembled button battery at room temperature are shown in Table 1. After 100 cycles, the capacity retention rate is 96.5%.

[0089] Table 1 Cyclic performance of the batteries obtained in the examples and comparative examples

[0090]

[0091] As can be seen from Table 1, the table is divided into three groups according to the different positive electrode materials in the technical solutions, that is, Comparative Example 2 corresponds to Examples 5 to 6, Comparative Example 3 corresponds to Examples 7 to 8, and Comparative Example 4 corresponds to Examples 9 to 10. It can be seen that in each group, the discharge capacity retention rate of the battery obtained in the embodiment after 100 cycles is better than that of the comparative example.

Claims

1. A surface treatment agent for a lithium ion positive electrode material, characterized in that: Includes monosaccharides and oligosaccharides.

2. The surface treatment agent for lithium ion positive electrode material according to claim 1, characterized in that The monosaccharide includes one or more of aldose and ketose; the oligomeric sugar substances include one or more of lactose, oligofructose, maltose, cellobiose, trehalose and raffinose.

3. The surface treatment agent for lithium ion positive electrode material according to claim 1, characterized in that The sugar ring of the surface treatment agent contains -OH and -CH2OH hydrophilic groups; the surface treatment agent includes a chain structure composed of sugar rings; the chain structure includes a branched chain structure and an unbranched chain structure; the protons on the hydroxyl groups in the chain structure can be Li + 、Na + , Ca + , K + The metal ions are substituted to form the corresponding alcohol salts.

4. Use of a surface treatment agent for a lithium ion positive electrode material according to any one of claims 1 to 3, characterized in that: The method of using the surface treatment agent to treat and prepare a positive electrode material for a battery comprises the following steps: S1. The surface treatment agent is dissolved in water at a set mass ratio, and after complete dissolution, the positive electrode material of the battery is added, and stirred at a preset temperature until the water is completely evaporated to obtain material 1; S2. Dry the material 1 obtained in step S1 in an oven to obtain a surface-treated battery positive electrode material.

5. The use of the surface treatment agent for lithium ion positive electrode material according to claim 4, characterized in that: Step S1 also includes using a spray drying process to treat the surface treatment agent of the lithium ion positive electrode material and the battery positive electrode material.

6. The use of the surface treatment agent for lithium ion positive electrode material according to claim 4, characterized in that: In step S1, the set mass ratio is 0.1-1%; the preset temperature is 40-80°C; the battery positive electrode material is at least one of LiXO2, LiY2O4, and LiZPO4; wherein X is at least one of Ni, Mn, and Co; Y is at least one of Ni and Mn; and Z is at least one of Fe and Mn.

7. The use of the surface treatment agent for lithium ion positive electrode material according to claim 4, characterized in that: In step S1, the battery positive electrode material includes lithium iron phosphate LiFePO4, lithium iron manganese phosphate LiMn x Fe 1-x O4, lithium manganese oxide LiMn2O4, lithium nickel manganese oxide LiNi 0.5 Mn 1.5 O4, nickel-cobalt-manganese ternary material LiNi x Co y Mn 1-x-y One or more of O2 and lithium cobalt oxide LiCoO2.

8. The use of the surface treatment agent for lithium ion positive electrode material according to claim 4, characterized in that: The battery positive electrode material also includes lithium manganese iron phosphate LiFe 0.4 Mn 0.6 PO4, lithium manganese oxide LiMn2O4, lithium nickel manganese oxide LiNi 0.5 Mn 1.5 O4, medium nickel ternary LiNi 0.5 Co 0.2 Mn 0.3 O2, lithium cobalt oxide LiCoO2 or one or more thereof.

9. The use of the surface treatment agent for lithium ion positive electrode material according to claim 4, characterized in that: The battery positive electrode material also includes lithium manganese iron phosphate LiFe 0.4 Mn 0.6 PO4, LiNi nickel manganese oxide 0.5 Mn 1.5 O4, lithium cobalt oxide LiCoO2 and medium nickel ternary LiNi 0.5 Co 0.2 Mn 0.3 O2.

10. The use of the surface treatment agent for lithium ion positive electrode materials according to claim 4, characterized in that: Step S2 specifically comprises: drying the material 1 obtained in step S1 at 100-150° C. for 6-24 hours to obtain a surface-treated battery positive electrode material.

Citation Information

Patent Citations

  • Preparation method of low-cost high-performance lithium iron phosphate material

    CN106099103A

  • Sn / C composite negative electrode material for lithium ion battery and preparation method thereof

    CN112510177A

  • Lithium ion battery and electronic device

    CN117638200A

  • Cadmium negative plate

    JP1987024560A

  • Nonaqueous electrolyte secondary battery

    JP2000021443A